Antioxidant and Antiaging Activity of Ethanolic Extract of Red Beetroot (Beta vulgaris L.): An In Vitro Study - Aji Winanta; Maitsa Via Saffriza (Sanata Dharma University, 2024)
Aging is a process of gradual changes in the skin caused by intrinsic and extrinsic factors. Intrinsic and extrinsic aging is the effect of increasing the reactive oxygen species (ROS) produced by cells resulting in cell damage. The use of natural materials has expanded for skin damage therapy, one of which is the utilization of red beetroot (Beta vulgaris L.). This study aims to discover the antioxidant and antiaging activity of Beta vulgaris L. in vitro. The process begins with the extraction of the maceration method using 70% ethanol as a solvent followed by identification of secondary metabolite compounds by phytochemical screening. Antioxidant activity test used the DPPH method with quercetin as a comparison. Antiaging activity testing was conducted in vitro with cell viability test using Human Dermal Fibroblast adult (HDF-a) by MTT Assay and the inhibitory effect of skin degradation enzymes (antiaging) was carried out with elastase using Human Neutrophil Elastase (HNE). The result of phytochemical screening tests showed Beta vulgaris L. contains alkaloids, saponins, and triterpenoid compounds. Red beetroot extract has weak antioxidant activity with IC50 of 3284.42 μg/mL. Antiaging activity testing showed that the extract can maintain cell viability and has the inhibitory activity of the enzyme elastase. This study concludes that red beetroot extract (Beta vulgaris L.) has potential as a cosmetic active ingredient for antiaging.